A EDUCAÇÃO AMBIENTAL PARA OS TRABALHADORES COMO INSTRUMENTO DE GESTÃO PARA O LICENCIAMENTO AMBIENTAL EM ATIVIDADES DE EXPLORAÇÃO E PRODUÇÃO DE PETRÓLEO OFFSHORE - Magalhães, Aldo de Brito (2005)
This study presents a workers training as a tool for the environmental licensing of the impact operations at offshore petroleum exploration process. This work shows a pilot training for the workers on the Environment Education, in the aim of launching a behavior change on activities related to ducts and sub sea equipments, realized on the Campos Basin, Rio de Janeiro, Brazil. The training figures out workers best practices and environmental awareness to execute those operations, based on a new knowledge and new behavior. The pilot project was validated by the target group - the trained workers - in a participatory methodology, in order to check if the training processes affect upon their behavior changes on the petroleum exploration and production underwater activities, supported by vessels. This project is being realized to attend the legal requirements at the environmental licensing process, by the increasing of the training management process,.